Literature Study on the Integration of Local Language and Culture in Urban Education in Makassar - Rahmawati, Rahmawati; Arsyad, Yolandika (Journal of Indonesian Progressive Education, 2026)
This study aims to analyze the integration of local language and culture in the urban education system in Makassar City through a library research approach with qualitative methods. The city of Makassar as a multicultural region faces the challenges of modernization and globalization which has led to a shift in the use of regional languages and the weakening of local cultural values such as siri' na pacce, sipakatau, and sipakainge. Based on the results of the literature analysis, it was found that local language and culture have a strategic role in shaping students' identities, strengthening character, and increasing the relevance of learning. This integration can be done through the application of local content based on ethnopedagogy, the development of contextual teaching materials, and collaboration between schools, cultural communities, and local governments. However, its implementation still faces challenges in the form of limited national curriculum, low teacher competence in implementing local cultural values, and lack of education policy support. Therefore, a policy strategy is needed that supports a curriculum based on local wisdom and increases the capacity of teachers to create contextual and culturally rooted learning. The results of this study are expected to make a theoretical and practical contribution to the development of ethnopedagogy-based education in urban areas such as Makassar.